0402 Incorporating more detailed exposure assessment with quantitative estimates is assessing the burden of occupational cancer. (23rd June 2014) - Demers, Paul; Peters, Cheryl; Davies, Hugh; Kim, Joanne; Pahwa, Manisha; McLeod, Chris; Nicol, Anne-Marie; Labreche, France; Lavoue, Jerome; Hutchings, Sally; Rushton, Lesley
Abstract : Objectives: In recent years, several new burden projects have been initiated with increased methodological sophistication. Previous studies have varied with respect to methods used to identify the prevalence and relevant levels of exposure, but many have relied on CAREX estimates. In this presentation, we will focus on the impact of incorporating more detailed exposure assessments with quantitative estimates as part of the Canadian burden of cancer project. Method: The Canadian exposure estimation process relies on data from CAREX Canada, taking into account industry and occupation at a more detailed level than previously. For many common carcinogens, the Canadian Workplace Exposure Database is used to account for changes in exposure levels over time and quantitative exposure-response relationships from the literature are used to assign relative risks relevant to the mean level of each exposure group. Historical employment trends are based upon census data at multiple time-points with province, sex, industry, and occupation detail. Results: Developing estimates for approximately 300 industries, as well as by occupation, and the need for estimating the age and gender characteristics of predicted cases to estimate economic burden, has also increased the complexity of estimating historic labour force dynamics. Annual labour force data 1976–2010 is used to attribute age- and tenure-distribution characteristics by province, sex, and industry. Conclusions: Although our main objective was to increase the validity of the burden estimation process, the more detailed exposure estimates allow us to calculated cancer burden for much more specific industry sectors and occupations, allowing for detailed risk reduction strategies.